Formulation and Evaluation of Domperidone Nanoemulsions for Oral Rout - Mohanad N. Taher; Ahmed A.Hussein (College of Pharmacy University of Baghdad, 2017)
The aim of the present study is to formulate, evaluate and characterize the nanoemulsion of Domperidone a poorly water-soluble anti-emetic drug.            Domperidone powder is white or almost white powder, photosensitive, practically insoluble in water, slightly soluble in ethanol and in methanol; soluble in dimethylformamide. It is used as an antiemetic for the short-term treatment of nausea and vomiting of various etiologies.            Solubility studies were conducted to select the oil, surfactant and cosurfactant. Phase diagrams were constructed by aqueous phase titration method. Formulations were selected from the phase diagrams. The formulations were characterized for particle size, Polydispersity index (PDI), zeta potential and in vitro drug release.           All the formulations were in nanoscale and Formula 1 (which contain anise oil as oil phase ,mixture of Surfactant Tween 80 and  cosurfactant (ethanol) at ratio 1:1  in addition to double distilled water as aqueous phase in ratio 1:6:3 respectively ) was the selected formula depending on particle size, PDI, zeta potential and in vitro drug release.          The Formula 1 has the best ratio because it gives the smallest nanoemulsion globule size (Particle size Average 20.81nm) and the best homogenicity (lowest PDI 0.266) and highest stability (higher zeta potential -33.9). The selected formula gives accepted physical and chemical properties. Keywords :Nanoemulsion, Domperidone.